2015
DOI: 10.1002/apj.1869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N2 pretreatment on the basicity, structural change, and isomerization activity of MgO and MgO/Mg(OH)2 catalysts

Abstract: As revealed by the X-ray diffraction, basicity titration, and Fourier transform infrared spectroscopy results, changes in the structural properties, basicity, and isomerization activities were observed on the MgO catalysts upon N 2 pretreatment at 325°C followed by isomerization reaction at 125°C. These changes became less pronounced when the starting catalysts contained Mg(OH) 2 phase or when the catalysts were pretreated under N 2 at high temperature alone (without reaction). Because of the limited amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…7. The peaks at wavenumber 3618, 3646, 3696, 3698, 3723 and 3726 cm -1 corresponded to OH groups of the Mg(OH)2 structure [8]. For the MgO(CP) and MgO(SV), these OH peaks were higher for the spent catalysts compared to the fresh ones.…”
Section: Restructuring Of Mgo Catalysts After 1-butene Isomerizationmentioning
confidence: 96%
See 1 more Smart Citation
“…7. The peaks at wavenumber 3618, 3646, 3696, 3698, 3723 and 3726 cm -1 corresponded to OH groups of the Mg(OH)2 structure [8]. For the MgO(CP) and MgO(SV), these OH peaks were higher for the spent catalysts compared to the fresh ones.…”
Section: Restructuring Of Mgo Catalysts After 1-butene Isomerizationmentioning
confidence: 96%
“…The isomerization activity of MgO, however, has often been found to be related to the presence of some specific low coordinated sites such as step, edge, and corner sites. A recent study from our group showed that rearrangement of the MgO structure occurred upon N2 pretreatment at 325 o C followed by isomerization reaction at 125 o C [8]. Thus, it is interesting to investigate how the restructuring of MgO catalysts may affect the performances of the MgO admixed with W-based catalysts in the metathesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the basicity, pore volume, and average pore size changed under different pre-treatment temperature conditions, resulting in different catalytic activities of the MgO catalyst and different activation energies as well. 36 Moreover, the differences may be due to differences in the transport phenomena involving pore and bulk diffusion and ow in the reactor. A U-tube reactor, xed bed reactor, and Berty-type reactor were used in work by Baird and Lunsford (1972), by Kasempremchit et al (2016), and in our research, respectively.…”
Section: Selection Of the Kinetic Modelmentioning
confidence: 99%